Automated discovery of concepts from text - Ong, Siou Chin (Faculty of Computer Science and Information Technology, 2008)
The proposed framework combines machine learning and semantic modeling in enabling the discovery process. The framework enables the extraction of concepts and the formulation of a structured organization and labeling of concepts to be used by text processing applications such as text summarization and text categorization.